Peningkatan keterampilan membaca puisi melalui penggunaan model pembelajaran cooperative script pada kelas IV sekolah dasar - Tri Wulandari; Rukayah Rukayah; Jenny Indrastoeti Siti Poerwanti (Didaktika Dwija Indria, 2019)
The purpose of this research is to improve poetry reading skills through the use of cooperative script learning models. Data collection technique are using test, interview, observation,and documentation. Data validity test are using content validity, source trianggulation, and technique trianggulation. Data analysis technique used is the interactive analysis and descriptive comparative. The results showed the average value of pre-action class 61.80, cycle I 72.29, and in the second cycle 81.31. Pre-action classical completeness 27.78%, first cycle 55.56%, and in the second cycle 83.33%. The value of the pre-action pronunciation is 15.27, the first cycle is 18.19, and the second cycle is 19.58. The value of the pre-action intonation is 14.44, the first cycle was 16.94, and the second cycle was 19.02. The value of the pre-action expression is 15.83, the first cycle is 18.96, the second cycle is 21.64. The value of the pre-action appreciation is 16.25, the first cycle is 18.33, and the second cycle is 21.04. Based on the result of the research, it can be concluded that through the use of cooperative script learning models can improve the poetry reading skills for fourth grade students of SD N Kismantoro 2 Wonogiri in the academic year 2018/2019.